PERAN POLITIK PENDIDIKAN ISLAM DALAM MENYUSUN KURIKULUM PENDIDIKAN AGAMA ISLAM MENUJU PENDIDIKAN ABAD XXI - IHWANUDDIN IHWANUDDIN (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2017)
Islamic education of curriculum is soft ware humanist mindset of Indonesian society which must be organized and perfected. Islamic education of curriculum given to each learner even educators in order to create a pleasant learning aqidah, syariah (Iman, Islam, Ihsan) and appreciate, that education in the XXI century reached the meaningfulness and even heat balance and the cruel demands of a globalized world. In the context of globalization, education should be able to maintain the cultural and national identity in the midst of the incessant onslaught of diverse cultures and civilizations of other nations. For this the policy makers must do the hard work to make education a format value and a reflection of civilization. Political Islamic education must play in order to manifest the demands of the XXI century. Political Islamic education spawned new policies in Islamic education that represents the ideology and philosophy of a nation so that the people educated and motivated to face the XXI century as evidence of their efforts and ways of thinking of the nation's most beautiful quality. Political Islamic education should be raised and echoed in every activity of life, especially in taking any educational policy. Pursued education policy serve as an instrument in addressing any educational activity that is easily understood and implemented education of every citizen education. Political Islamic education serve as the basis of philosophical and ideological education in carrying out activities to develop Islamic education of curriculum. The Islamic education of curriculum oriented education model and view in education, namely God's creatures by nature. Islamic education of curriculum beings live, should be able to establish, maintain, and develop their life. In this case the position of education is expected to build the process of education